Model Muhadatsah Yaumiyyah untuk Meningkatkan Kemahiran Bahasa Arab Santriwati Kelas XI SMA IT Ibnu Abbas Klaten - Arianto ferzan arman (Taqdir, 2023)
Teaching Arabic is a tough challenge for some teachers. Not infrequently they encounter difficulties and obstacles when explaining material to students. Therefore, teachers are required to be able to choose the right learning media and models so that students are not bored and are happy with their interest in learning Arabic. Advances in technology provide fresh air for teachers, because there are many learning media and models that can be used, one of which uses the yaumiyah muhadasah model. This study aims to explain the process of using the yaumiyah muhadasah model to improve female students' Arabic language proficiency at Tahfidz Qur'an Ibnu Abbas Islamic Boarding School and their responses during learning. This research uses a qualitative research method with a field study approach. Data collection was carried out by observation, interviews and documentation studies and then analyzed by observation during learning activities using the yaumiyah muhadasah model. The results of this study are that the yaumiyah muhadasah model can be used as an interesting medium for learning Arabic and can improve Maharahkalam Arabic proficiency and make students more enthusiastic about memorizing dialogue and understanding its mufradat. Keywords: Muhadatsah, Yaumiyyah, Maharah